The story of the Trail of Tears - Stein, R. Conrad; Catrow, David J. (Chicago : Childrens Press, 1985)
Describes the Federal government's seizure of Cherokee land in Georgia and the forced migration of the Cherokee Nation along the Trail of Tears to Oklahoma.
Includes index.
6.9
3-6
Keywords: Cherokee Removal, 1838 -- Juvenile literature; Cherokee Indians -- History -- Juvenile literature; Cherokee Removal, 1838.; Cherokee Indians -- History; Indians of North America -- Southern States -- History; Cherokee Indians -- Removal, 1838.; Cherokee Indians -- History; Indians of North America -- Southern States